2005
DOI: 10.1099/vir.0.80436-0
|View full text |Cite
|
Sign up to set email alerts
|

The human cytomegalovirus UL78 gene is highly conserved among clinical isolates, but is dispensable for replication in fibroblasts and a renal artery organ-culture system

Abstract: The human cytomegalovirus UL78 gene is highly conserved among clinical isolates, but is dispensable for replication in fibroblasts and a renal artery organ-culture system The human cytomegalovirus (HCMV) UL78 ORF is considered to encode a seven-transmembrane receptor. However, neither the gene nor the UL78 protein has been characterized so far. The objective of this study was to investigate the UL78 gene and to clarify whether it is essential for replication. UL78 transcription was activated early after infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…They have found substantial variation in the sequences of the many conserved ORFs. Mertens and collaborators (29) reported that although the HCMV UL78 gene was highly conserved among clinical isolates, the gene was dispensable for replication in fibroblasts and a renal artery organculture system. Ruan and coworkers (22) have reported the occurrence of sequence variation caused by frameshift mutations found in the UL143 gene in all HCMV clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…They have found substantial variation in the sequences of the many conserved ORFs. Mertens and collaborators (29) reported that although the HCMV UL78 gene was highly conserved among clinical isolates, the gene was dispensable for replication in fibroblasts and a renal artery organculture system. Ruan and coworkers (22) have reported the occurrence of sequence variation caused by frameshift mutations found in the UL143 gene in all HCMV clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis has shown that HCMV pUL78 is not required for normal viral growth in fibroblasts or in a renal artery tissue culture model (15). To investigate the possibility that the viral GPCR is needed for replication in other cell types, we generated a pUL78-deficient derivative of a clinical strain of HCMV with broad host cell tropism.…”
mentioning
confidence: 99%
“…Previous studies on herpesvirus 7-transmembrane (7-tm) receptors have generally concluded that these genes are dispensable for in vitro replication of virus; examples include HCMV US28 (52), HCMV UL33 (30), mouse CMV (MCMV) M33 (15), rat CMV (RCMV) R33 (6), and HCMV UL78 (32). However, deletion of the MCMV M78 gene has been shown to reduce virus replication in cultured fibroblasts (37), and deletion of the RCMV R78 gene also results in attenuation of virus production in cell culture systems (5,28).…”
Section: Discussionmentioning
confidence: 99%